’No, I’m a stranger here, I belong somewhere else!’ Alienation in the literary work of Anna Mitgutsch - Jurzysta, Aneta (Acta Universitatis Lodziensis. Folia Germanica, 2016)
The paper deals with the broad concept of strangeness in the literary work of Anna Mitgutsch, a contemporary Austrian writer. The topic of strangeness is a keynote in her rich literary output. Mitgutsch’s experience of being abroad (travelling to the Middle East and south-east Asia, living and working in Israel, England, Korea and The USA) is reflected in such novels as Das andere Gesicht, In fremden Städten or Abschied von Jerusalem. Her characters are nomads, people looking for identity and homeland, trying to escape alienation. The feeling of being a stranger is also present in their relations with their loved ones (Die Annäherung).